Pengaruh Sistem Informasi Akuntansi, Kualitas Sumber Daya Manusia, Kemampuan Menyusun Laporan Keuangan, dan Pemanfaatan E-Commerce Terhadap Kinerja Usaha Mikro, Kecil, dan Menengah (UMKM) - Vanda Tri Ulansari; Nurharibnu Wibisono; Arini Wildaniyati (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2024)
This research aims to examine the influence of Accounting Information Systems, Quality of Human Resources, Ability to Prepare Financial Reports and Utilization of E-Commerce on the Performance of Micro, Small and Medium Enterprises (MSMEs). The type of research used in this research is quantitative with a descriptive approach.. Data was obtained by distributing it directly to MSMEs and using Google Form. The population in this research is Micro, Small and Medium Enterprises (MSMEs) in Madiun City, especially the Kartoharjo District area.. The sampling method used was a purposive sampling technique with a total of 100 respondents. Data analysis was carried out using multiple linear regression analysis with the SPSS (Statistical Product and Service Solution) version 25 for Windows program. The results of the hypothesis research show that the Accounting Information System independence variable is 0.001, the Quality of Human Resources variable is 0.003, the Ability to Prepare Financial Reports variable is 0.005, E-Commerce Utilization is 0.000 and the Adjusted R Squre shows a value of 0.702 or 70.2%. With these results it can be stated that the Accounting Information System, Quality of Human Resources, Ability to Prepare Financial Reports and Utilization of E-Commerce have a positive and significant effect on the performance of Micro, Small and Medium Enterprises (MSMEs).